2019
DOI: 10.1080/02699931.2019.1577220
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Radboud faces database from a child’s perspective

Abstract: Facial expressions play a central role in diverse areas of psychology. However, facial stimuli are often only validated by adults, and there are no face databases validated by school-aged children. Validation by children is important because children still develop emotion recognition skills and may have different perceptions than adults. Therefore, in this study, we validated the adult Caucasian faces of the Radboud Faces Database (RaFD) in 8-to 12-year-old children (N = 652). Additionally, children rated vale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…As the current study was part of a larger project focused at assessing emotion processing, social processes and childhood anxiety, the children also completed other measures (a full list of all the measures can be obtained from the authors). Two other published papers about different topics were based on the same participant group [40, 41]. The current study was conducted in 11 of the 15 schools among 605 children.…”
Section: Methodsmentioning
confidence: 99%
“…As the current study was part of a larger project focused at assessing emotion processing, social processes and childhood anxiety, the children also completed other measures (a full list of all the measures can be obtained from the authors). Two other published papers about different topics were based on the same participant group [40, 41]. The current study was conducted in 11 of the 15 schools among 605 children.…”
Section: Methodsmentioning
confidence: 99%
“…Although no specific socioeconomic data were collected, participants were drawn from regular elementary schools in both urban and rural parts of the country suggesting that the sample may be representative of the broader population. The current study was part of a larger study on childhood anxiety (Mobach et al, 2019;Verpaalen et al, 2019) and was approved by the Ethical Committee of the Social Sciences Department of Radboud University Nijmegen in the Netherlands.…”
Section: Participantsmentioning
confidence: 99%
“…In the first case, despite the significant cross-cultural differences in the classification of emotions that should be taken in account, the authors found high recognition agreement rates [ 52 ], which were similar to the ones reported in the original study by Langner et al (2010) [ 32 ]. In the second case, children’s emotion recognition pattern was identical to the adults’ pattern, although children were less able to distinguish between similar emotions [ 54 ]. In another study, Dawel et al (2017) pointed out that an advantage of the RaFD database was the availability of genuineness ratings [ 55 ].…”
Section: Introductionmentioning
confidence: 99%